Increasing of accuracy for engineering calculation of heat transfer problems in two layer media - Kalis, H.; Kangro, I. (Mathematical Modelling and Analysis, 2005)
In this paper we study the simple algorithms for modelling the heat transfer problem in two layer media. The initial model which is based on a partial differential equation is reduced to ordinary differential equations (ODEs). The increase of accuracy is shown if instead of first order ODE initial value problem ([4, 5]) the second order differential equations is taken. Such a procedure allows us to obtain a simple engineering algorithm for solving heat transfer equations in two layered domain of Cartesian, cylindrical (with axial symmetry) and spherical coordinates (with radial symmetry). In a stationary case the exact finite difference scheme is obtained.Kai kurių inžinerinių, dvisluoksnėje srityje, šilumos laidumo uždavinių tikslumo didinimasŠiame straipsnyje yra nagrinėjami paprasti dvisluoksnės srities šilumos laidumo problemos modeliavimo algoritmai, keičiant diferencialines lygtis dalinėmis išvestinėmis į paprastas diferencialines lygtis. Parodoma, kad didesnio tikslumo pasiekimui, vietoje pirmos eilįs paprastų diferencialinių lygčių pradinio uždavinio nagrinėjamos antros eilės diferencialinės lygtys. Ši procedūra leidžia gauti paprastą inžinerinį dvisluoksnės srities šilumos laidumo lygties sprendinė stačiakampėje, cilindrinėje (su ašių simetrija) ir sferinėje (su spinduline simetrija) koordinačių sistemoje. Tiksli baigtinių skirtumų schema buvo sudaryta stacionariam atvejui.First Published Online: 14 Oct 2010